Secondary battery and preparation method and device thereof

By using a modified layer composed of polymer, lithium salt and inorganic particles in the secondary battery, the problem of insufficient interface contact between the solid electrolyte and the electrode is solved, and the circulation performance and stability are significantly improved.

CN119324247APending Publication Date: 2025-01-17NIO BATTERY TECH (ANHUI) CO LTD
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202310879999.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-17
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The interface contact area between the solid electrolyte and the positive electrode sheet and the negative electrode sheet in the secondary battery is small, the impedance is large, and the stability is poor, resulting in poor circulation performance.

Method used

The first modification layer and the second modification layer including 20% ​​to 60% by weight of polymer, 10% to 65% by weight of lithium salt and 2% to 45% by weight of inorganic particles are used, and are located between the positive electrode sheet and the solid electrolyte and the negative electrode sheet and the negative electrode sheet and the Between solid electrolytes, interface defects and resistance are reduced, side reactions are avoided, and thermal stability is improved.

Benefits of technology

It significantly reduces the internal interface resistance of the secondary battery, improves cycling performance and lithium stability, and extends the battery's service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004357857040000171
    Figure BDA0004357857040000171
  • Figure BDA0004357857040000181
    Figure BDA0004357857040000181
  • Figure BDA0004357857040000191
    Figure BDA0004357857040000191
Patent Text Reader

Abstract

The invention provides a secondary battery and a preparation method and device thereof, and the secondary battery comprises a positive pole piece, a negative pole piece, a solid electrolyte, a first modification layer and a second modification layer. One of the first modification layer and the second modification layer is located between the positive pole piece and the solid electrolyte, and the other one of the first modification layer and the second modification layer is located between the negative pole piece and the solid electrolyte; the first modification layer and / or the second modification layer comprises 20 wt%-60 wt% of polymer, 10 wt%-65 wt% of lithium salt and 2 wt%-45 wt% of inorganic particles. The thickness of the first modification layer and / or the second modification layer is relatively thin, easy to control and relatively good in uniformity, so that the interface resistance between the positive pole piece and / or the negative pole piece in the secondary battery and the solid electrolyte is remarkably reduced, the side reaction between the solid electrolyte and the positive pole piece and / or the negative pole piece is avoided, and the service life of the secondary battery is prolonged. And the first modification layer and / or the second modification layer have / has good thermal stability, so that the cycle performance of the secondary battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of energy storage, and specifically to a secondary battery and a preparation method and device thereof. Background Art

[0002] Secondary batteries are gaining more and more attention due to their advantages such as high safety performance, high energy density, long cycle life, wide operating temperature range, wide electrochemical window and flexibility. However, in secondary batteries, solid electrolytes are used instead of electrolytes. Due to the poor fluidity of solid electrolytes, the solid-solid interface between the solid electrolyte and the positive and negative electrode sheets has a small contact area, large impedance and poor stability. In addition, due to the incompatibility of solid electrolyte materials with electrode materials, a space charge layer will be formed between the positive electrode sheet and the solid electrolyte, and diffusion and reaction between the positive electrode material and the solid electrolyte will easily occur; the volume change of solid electrolyte materials during charging and discharging will also cause interfacial stress between the solid electrolyte and the electrode sheet; the negative electrode sheet (for example, a metal lithium negative electrode sheet with strong reducibility) and the solid electrolyte will easily react, resulting in poor cycle performance of the secondary battery, thereby limiting the practical application of secondary batteries.

[0003] Therefore, we urgently need to find a method to solve the poor interface of secondary batteries. Summary of the invention

[0004] In view of the above problems existing in the prior art, the present application provides a secondary battery and a method and device for preparing the same.

[0005] The first aspect of the present application provides a secondary battery, including a positive electrode sheet, a negative electrode sheet, a solid electrolyte, a first modification layer and a second modification layer; one of the first modification layer and the second modification layer is located between the positive electrode sheet and the solid electrolyte, and the other of the first modification layer and the second modification layer is located between the negative electrode sheet and the solid electrolyte; the first modification layer and / or the second modification layer include a polymer with a mass content of 20wt% to 60wt%, 10wt% to 65wt% of lithium salt, and 2wt% to 45wt% of inorganic particles. The first modification layer and the second modification layer of the present application are conducive to reducing the interface defects between the positive electrode sheet and / or the negative electrode sheet and the solid electrolyte, significantly reducing the interface resistance between the positive electrode sheet and / or the negative electrode sheet and the solid electrolyte in the secondary battery, effectively avoiding the side reaction between the solid electrolyte and the positive electrode sheet and / or the negative electrode sheet, and the first modification layer and the second modification layer have good thermal stability, therefore, it is also conducive to improving the cycle performance of the secondary battery.

[0006] The second aspect of the present application provides a method for preparing a secondary battery, which is used to prepare the aforementioned secondary battery. The preparation method includes: step 1, mixing a mixture including a polymer with a mass content of 20wt% to 60wt%, a lithium salt of 10wt% to 65wt% and an inorganic particle of 2wt% to 45wt% with a solvent, to prepare a polymer composite solution; step 2, applying the polymer composite solution obtained in step 1 to one side of the solid electrolyte surface, removing excess solvent, and obtaining a first modification layer; step 3, forming a second modification layer on the other side of the solid electrolyte surface. The preparation method of the present application is simple to operate, and the thickness of the first modification layer and / or the second modification layer is thin and easy to control, and the uniformity is good. At the same time, it can ensure that the inorganic particles in the first modification layer and / or the second modification layer are evenly distributed, and the first modification layer and / or the second modification layer are in-situ solidified on the surface of the solid electrolyte, which can effectively improve the contact between the positive electrode plate and / or the negative electrode plate and the solid electrolyte, thereby effectively reducing the interface impedance. In addition, since the first modified layer and / or the second modified layer prepared by the preparation method of the present application is thinner and has excellent ion conductivity, it is also beneficial to shorten the transmission distance of lithium ions. Moreover, combined with the introduction of the first modified layer and the second modified layer to optimize the interface performance of the secondary battery, the cycle performance of the secondary battery is significantly improved.

[0007] A third aspect of the present application provides a device comprising the aforementioned secondary battery. DETAILED DESCRIPTION

[0008] In order to make the purpose, technical scheme and advantages of the present application clearer, the technical scheme of the present application will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. The relevant embodiments described herein are illustrative and are used to provide a basic understanding of the present application. The embodiments of the present application should not be interpreted as limiting the present application.

[0009] For simplicity, only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.

[0010] In the description herein, unless otherwise specified, “above” and “below” include the number.

[0011] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values ​​of the various parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application).

[0012] A list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components. The terms "first," "second," etc. do not have special meanings and are only used to distinguish different structures, and are not used to limit the scheme of the present application.

[0013] The present application is further described below in conjunction with specific implementations. It should be understood that these specific implementations are only used to illustrate the present application and are not used to limit the scope of the present application.

[0014] Primary and secondary batteries

[0015] One or more embodiments of the present application provide a secondary battery, including a positive electrode sheet, a negative electrode sheet, a solid electrolyte, a first modification layer and a second modification layer; one of the first modification layer and the second modification layer is located between the positive electrode sheet and the solid electrolyte, and the other of the first modification layer and the second modification layer is located between the negative electrode sheet and the solid electrolyte; the first modification layer and / or the second modification layer include a polymer with a mass content of 20wt% to 60wt%, a lithium salt of 10wt% to 65wt%, and an inorganic particle of 2wt% to 45wt%. The first modification layer and / or the second modification layer of the present application are beneficial to reducing the interface defects between the positive electrode sheet and / or the negative electrode sheet and the solid electrolyte, significantly reducing the interface resistance between the positive electrode sheet and / or the negative electrode sheet and the solid electrolyte in the secondary battery, effectively avoiding the side reaction between the solid electrolyte and the positive electrode sheet and / or the negative electrode sheet, and the first modification layer and / or the second modification layer have good thermal stability, therefore, it is also beneficial to improve the cycle performance of the secondary battery.

[0016] It is understood that the first modified layer and the second modified layer of the present application may be the same or different, and at least one of the first modified layer and the second modified layer of the present application includes a polymer having a mass content of 20wt% to 60wt%, a lithium salt of 10wt% to 65wt%, and an inorganic particle of 2wt% to 45wt%. Any one of the first modified layer and the second modified layer of the present application may also be formed by dripping an electrolyte or an ionic liquid on the surface of a solid electrolyte. The present application does not impose any specific restrictions on the composition of the electrolyte and the ionic liquid, as long as it is conducive to the transmission of lithium ions and makes the insertion and extraction of lithium ions more matched, and / or, can optimize the interface between the solid electrolyte and the positive electrode sheet and / or the negative electrode sheet.

[0017] In other embodiments, the secondary battery of the present application may also include only one of the first modification layer and the second modification layer, and the other of the first modification layer and the second modification layer does not exist, as long as the lithium ion transfer balance at the positive electrode plate and the negative electrode plate in the secondary battery is ensured.

[0018] It is understood that the secondary battery of the present application includes a solid-state battery that realizes lithium ion exchange between the positive electrode plate and the negative electrode plate by a solid electrolyte, a liquid battery that realizes lithium ion exchange between the positive electrode plate and the negative electrode plate by a combination of a diaphragm and an electrolyte, and a combination of a solid-state battery and a liquid battery. The first modification layer and / or the second modification layer involved in the present application can also be applied to other positions besides the surface of the solid electrolyte according to specific needs.

[0019] In some embodiments, the first modification layer and / or the second modification layer comprises 30wt% to 50wt% of polymer, 20wt% to 50wt% of lithium salt and 20wt% to 40wt% of inorganic particles. By further controlling the mass ratio of each component in the first modification layer and / or the second modification layer, the uniformity of the first modification layer and / or the second modification layer can be further improved, and the toughness and rigidity of the first modification layer and / or the second modification layer can be balanced; it is beneficial to increase the contact area between the solid electrolyte and the electrode, and also beneficial to improve the structural stability of the secondary battery.

[0020] In some embodiments, the ionic conductivity of the first modified layer and / or the second modified layer at 60° C. is 1.5×10 - 3 S cm -1 ~5.0×10 -3 S cm -1 ; Exemplarily, the ionic conductivity of the first modified layer and / or the second modified layer is 1.5×10 -3 S cm -1 , 1.6×10 -3 S cm -1 , 1.8×10-3 S cm -1 , 2.0×10 -3 S cm -1 , 2.2×10 -3 S cm -1 , 2.4×10 -3 S cm -1 , 2.5×10 -3 S cm -1 , 2.6×10 -3 S cm -1 , 2.8×10 -3 S cm -1 , 3.0×10 -3 S cm -1 , 3.2×10 -3 S cm -1 , 3.3×10 -3 S cm -1 , 3.4×10 -3 S cm -1 , 3.5×10 -3 S cm -1 , 3.6×10 -3 S cm -1 , 3.8×10 -3 S cm -1 4.0×10 -3 S cm -1 4.2×10 -3 S cm -1 , 4.4×10 -3 S cm -1 , 4.5×10 - 3 S cm -1 , 4.6×10 -3 S cm -1 4.8×10 -3 S cm -1 5.0×10 -3 S cm -1 Or a range consisting of any two of the above values. By controlling the ionic conductivity of the first modified layer and / or the second modified layer at 60°C within the above range, an ideal interface phase of high ionic conductivity and low electronic conductivity can be achieved, the decomposition of the electrolyte under high pressure is suppressed, and the cycle stability of the secondary battery is improved. The applicant has found that by reasonably optimizing at least one of the type and / or content of the polymer, the type and / or content of the lithium salt, the type and / or content of the inorganic particles, and the uniformity of the first modified layer and / or the second modified layer, the ionic conductivity of the first modified layer and / or the second modified layer can be controlled within the above range.

[0021] In some embodiments, the thickness of at least one of the first modification layer and the second modification layer is 60 μm to 100 μm. Exemplarily, the thickness of at least one of the first modification layer and the second modification layer is 60 μm, 62 μm, 64 μm, 65 μm, 66 μm, 68 μm, 70 μm, 72 μm, 74 μm, 75 μm, 76 μm, 78 μm, 80 μm, 82 μm, 84 μm, 85 μm, 86 μm, 88 μm, 90 μm, 92 μm, 94 μm, 95 μm, 96 μm, 98 μm, 100 μm or a range consisting of any two of the above values. It is understood that if the thickness of the first modification layer or the second modification layer is too large, the transmission efficiency of lithium ions will be affected, and the cycle performance and power performance of the secondary battery will be affected; if the thickness of the first modification layer or the second modification layer is too small, the compatibility between the solid electrolyte and the positive electrode sheet or the negative electrode sheet cannot be effectively improved, and the stability to lithium cannot be effectively improved. Controlling the thickness of the first modified layer or the second modified layer within the above range is beneficial to improving the lithium stability, power performance and cycle performance of the secondary battery, thereby achieving improvement in the overall performance of the secondary battery.

[0022] In some embodiments, the first modified layer and the second modified layer both include polymers, lithium salts and inorganic particles in a mass ratio of (20% to 60%): (10% to 65%): (2% to 45%), and the first modified layer is located between the positive electrode plate and the solid electrolyte, the second modified layer is located between the negative electrode plate and the solid electrolyte, and the thickness ratio of the first modified layer to the second modified layer is 1:(1.00 to 1.67); illustratively, the thickness ratio of the first modified layer to the second modified layer is 1:1.00, 1:1.05, 1:1.1, 1:1.15, 1:1.2, 1:1.25, 1:1.3, 1:1.35, 1:1.4, 1:1.45, 1:1.5, 1:1.55, 1:1.6, 1:1.65, 1:1.67 or a range consisting of any two of the above ratios. It is understandable that the second modified layer between the negative electrode and the solid electrolyte is relatively thicker, which can better inhibit the growth of lithium dendrites and improve lithium stability. The first modified layer between the positive electrode and the solid electrolyte needs to meet the requirements of improving the interface and having good ionic conductivity. The first modified layer focuses more on the composition rather than the thickness. At the same time, considering the problem of interface transmission time, the first modified layer can be thinner than the second modified layer.

[0023] In other embodiments, the thickness of the first modification layer may also be greater than or equal to the thickness of the second modification layer.

[0024] In some embodiments, the average particle size of the inorganic particles is 20nm to 200nm. Exemplarily, the average particle size of the inorganic particles is 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm, 200nm or a range consisting of any two of the above values. It is understandable that the inorganic particles are small in size, corresponding to a larger specific surface area, which is more conducive to the conduction of lithium ions in the modified layer based on the percolation theory, so small-sized particles of nanometer scale are selected; however, due to the limitations of process technology and cost, inorganic particles less than 20nm are not conducive to mass production and industrial application; therefore, the average particle size of the inorganic particles is controlled within the above range.

[0025] In some embodiments, the average particle size of the inorganic particles is 30 nm to 150 nm; illustratively, the average particle size of the inorganic particles is 32 nm, 35 nm, 45 nm, 55 nm, 65 nm, 75 nm, 85 nm, 95 nm, 105 nm, 115 nm, 125 nm, 135 nm, 145 nm, 150 nm or a range consisting of any two of the above values.

[0026] In some embodiments, the inorganic particles include but are not limited to at least one of aluminum nitride, aluminum oxide, boron nitride, magnesium hydroxide, calcium hydroxide, and silicon dioxide. Introducing inorganic particles into the first modified layer and / or the second modified layer can effectively improve the mechanical strength of the first modified layer and / or the second modified layer, and effectively inhibit the formation of lithium dendrites. The excellent thermal stability and chemical stability of inorganic particles are also conducive to improving the safety performance of the battery. In addition, introducing inorganic particles into the first modified layer and / or the second modified layer can also improve the ionic conductivity of the first modified layer and / or the second modified layer, thereby increasing the diffusion rate of lithium ions in the first modified layer and / or the second modified layer. The type of inorganic particles is not limited to this, and can be any material that can achieve the above functions.

[0027] In some embodiments, the inorganic particles include boron nitride. Boron nitride has high mechanical strength, strong chemical and electrochemical stability, strong high temperature stability, and low expansion coefficient. After the introduction of boron nitride into the first modification layer and / or the second modification layer, the stability of the first modification layer and / or the second modification layer can be enhanced, thereby effectively inhibiting the side reaction between the positive electrode and / or the negative electrode and the solid electrolyte, and at the same time inhibiting the growth of lithium dendrites and improving the safety performance of the secondary battery.

[0028] In some embodiments, based on the total mass of the polymer and the inorganic particles, the mass content of the inorganic particles is 5wt% to 50wt%; illustratively, based on the total mass of the polymer and the inorganic particles, the mass content of the inorganic particles is 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt% or a range consisting of any two of the above values. If the relative content of the inorganic particles in the first modified layer and / or the second modified layer is too low, the intrinsic ionic conductivity of the first modified layer and / or the second modified layer is low, and the ion conduction ability is weak, which is not enough to effectively inhibit the growth of lithium dendrites, thereby affecting the cycle performance and safety performance of the battery. If the content of inorganic particles in the first modification layer and / or the second modification layer is too high, the inorganic particles are prone to agglomeration, resulting in uneven distribution of inorganic particles in the polymer, and the excessive content of inorganic particles will also increase the steric hindrance, thereby deteriorating the ionic conductivity and uniformity of the first modification layer and / or the second modification layer, and further, the first modification layer and / or the second modification layer cannot effectively improve the interface performance of the secondary battery. Therefore, controlling the content of inorganic particles in the first modification layer and / or the second modification layer within the above range is conducive to the inorganic particles to give full play to their own high mechanical strength and high stability characteristics, and is conducive to improving the interface contact between the positive electrode sheet and / or the negative electrode sheet and the solid electrolyte, and improving the lithium stability and safety of the secondary battery; it can also effectively improve the ionic conductivity of the first modification layer and / or the second modification layer, improve the lithium ion conduction ability, and further improve the cycle performance of the secondary battery.

[0029] In some embodiments, based on the total mass of the polymer and the inorganic particles, the mass content of the inorganic particles is 20wt% to 40wt%; exemplarily, based on the total mass of the polymer and the inorganic particles, the mass content of the inorganic particles is 21wt%, 22wt%, 23wt%, 24wt%, 26wt%, 27wt%, 28wt%, 29wt%, 31wt%, 32wt%, 33wt%, 34wt%, 36wt%, 37wt%, 38wt%, 39wt%, 40wt% or a range consisting of any two of the above values.

[0030] In some embodiments, the polymer includes, but is not limited to, at least one of polyvinylidene fluoride, polyethylene oxide, polyacrylonitrile, and polymethyl acrylate.

[0031] In some embodiments, the lithium salt includes but is not limited to at least one of lithium nitrate, lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide), lithium perchlorate, lithium difluorooxalatoborate, and lithium trifluoromethanesulfonate.

[0032] In some embodiments, the solid electrolyte includes, but is not limited to, at least one of a polymer solid electrolyte, an oxide solid electrolyte, and a sulfide solid electrolyte.

[0033] In some embodiments, the oxidative inorganic solid electrolyte includes, but is not limited to, at least one of a NASICON-type electrolyte, a garnet-type electrolyte, and a perovskite-type electrolyte.

[0034] In some embodiments, NASICON-type electrolytes include but are not limited to Li 1.3 Al 0.3 Ti 1.7 (PO4)3(LATP).

[0035] In some embodiments, garnet-type electrolytes include but are not limited to Li7La3Zr2O 12 .

[0036] In some embodiments, the perovskite electrolyte includes but is not limited to Li 0.35 La 0.55 TiO3.

[0037] In some embodiments, the positive electrode sheet of the present application includes: a positive electrode current collector and a positive electrode active material layer located on the surface of the positive electrode current collector, and the positive electrode active material of the positive electrode active material layer includes: at least one of a nickel-cobalt ternary material and a phosphate-based material; the nickel-cobalt ternary material includes LiNi x Co y M (1-x-y) At least one of O2 materials, M includes at least one of Mn, Al, Mg, Cr, Ca, Zr, Mo, Ag, Nb, 0.5≤x≤1, 0≤y≤0.5, x+y≤1; phosphate materials include LiMn k B (1-k) PO4, wherein 0≤k≤1, and the B element comprises at least one of iron, cobalt, magnesium, calcium, zinc, chromium or lead.

[0038] In some embodiments, the positive electrode active material layer further includes a conductive agent and a binder. The positive electrode active material, the conductive agent, and the binder are fully stirred and mixed in a solvent system in a certain proportion, and then coated on the positive electrode current collector, dried, and rolled to obtain a positive electrode sheet.

[0039] In some embodiments, the conductive agent includes, but is not limited to, carbon-based materials, metal-based materials, conductive polymers, and mixtures thereof. In some embodiments, the carbon-based material includes, but is not limited to, one of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material includes, but is not limited to, at least one of metal powder, metal fiber, copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer is a polyphenylene derivative.

[0040] In some embodiments, the binder includes but is not limited to at least one of polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin or nylon.

[0041] In some embodiments, the negative electrode plate of the present application includes: a negative electrode current collector and a negative electrode active material layer located on the surface of the negative electrode current collector, and the negative electrode active material of the negative electrode active material layer includes: at least one of silicon-based materials, carbon-based materials, tin-based materials, phosphorus-based materials, and metallic lithium. The silicon-based material includes at least one of silicon, silicon alloys, silicon oxide compounds, and silicon-carbon compounds, the carbon-based material includes at least one of graphite, soft carbon, hard carbon, carbon nanotubes, and graphene, the tin-based material includes at least one of tin, tin oxide, and tin alloys, and the phosphorus-based material includes phosphorus and / or phosphorus-carbon composites. In some embodiments, the negative electrode plate is metallic lithium.

[0042] 2. Preparation method of secondary battery

[0043] One or more embodiments of the present application further provide a method for preparing a secondary battery, which is used to prepare the secondary battery of the aforementioned embodiment, and the preparation method includes:

[0044] Step 1, adding a polymer, a lithium salt and inorganic particles in a mass ratio of (20% to 60%): (10% to 65%): (2% to 45%) to a solvent to prepare a polymer composite solution;

[0045] Step 2, coating the polymer composite solution obtained in step 1 on one surface of the solid electrolyte, removing excess solvent, and obtaining a first modified layer;

[0046] Step 3, forming a second modified layer on the other side surface of the solid electrolyte.

[0047] It is understandable that the method for forming the second modified layer can be the same as the method for forming the first modified layer, or it can be different, as long as the lithium ion transmission balance in the secondary battery can be guaranteed. The above preparation method is simple to operate, and the thickness of the first modified layer and / or the second modified layer obtained is thin and easy to control, and the uniformity is good. At the same time, it can ensure that the inorganic particles in the first modified layer and / or the second modified layer are evenly distributed, and the first modified layer and / or the second modified layer are in situ solidified on the surface of the solid electrolyte, which can effectively improve the contact between the positive electrode and / or the negative electrode and the solid electrolyte, thereby effectively reducing the interface impedance. In addition, since the thickness of the first modified layer and / or the second modified layer obtained by the above preparation method is thin and the ionic conductivity is excellent, it is also conducive to shortening the transmission distance of lithium ions, and, combined with the introduction of the first modified layer and the second modified layer for the optimization of the interface performance of the secondary battery, the cycle performance of the secondary battery is significantly improved.

[0048] In some embodiments, the coating method in step 2 includes spin coating. Compared with other coating methods, the spin coating process is convenient to operate, the film is formed quickly and evenly, and the problem of uneven film formation of the first modified layer can be effectively avoided. In addition, in the spin coating process, by controlling the types of components in the polymer composite solution and / or the content of each component in the polymer composite solution, the viscosity of the polymer composite solution and the degree of dispersion of each component in the polymer composite solution can be controlled; furthermore, the uniformity, ionic conductivity, thickness, etc. of the first modified layer can be controlled, and the interface transmission characteristics between the positive electrode plate or the negative electrode plate and the solid electrolyte can also be optimized to achieve a comprehensive improvement in the electrochemical performance and cycle performance of the secondary battery. In addition, in the prior art, it is generally believed by those skilled in the art that the modified layer containing polymer on the surface of the solid electrolyte is not suitable for preparation by spin coating, because the polymer is generally an insulating material. In order to ensure the conductivity of the modified layer, conductive substances such as electrolyte materials are usually added to the polymer; however, since the viscosity of the polymer itself is usually large, in order to ensure that the conductive substances such as electrolyte materials can be fully dispersed in the polymer, the concentration of the polymer in the modified layer precursor solution is extremely low, and it is difficult to form a film by spin coating. The preparation method of the present application overcomes the above prejudice. The first modified layer and / or the second modified layer prepared by the preparation method of the present application are thin and the inorganic particles are evenly distributed; and the first modified layer and / or the second modified layer are in-situ cured on the surface of the solid electrolyte, which can effectively improve the contact between the electrode and the solid electrolyte, and can more effectively reduce the interface impedance; in addition, the thinner and excellent ionic conductivity of the first modified layer and / or the second modified layer can also shorten the conduction distance of lithium ions; further, the first modified layer and / or the second modified layer can also optimize the interface performance between the solid electrolyte and the electrode of the secondary battery; thus, the cycle performance of the secondary battery can be improved. In addition, the preparation method of the present application is simple to operate and low in cost, which is conducive to commercial application.

[0049] In other embodiments, the coating method in step 2 may also include at least one of spraying, screen printing, casting or dipping.

[0050] In some embodiments, in step 1, preparing the polymer composite solution comprises the following steps:

[0051] Step 1-1, adding the polymer and the lithium salt into the solvent and stirring until they are completely dissolved;

[0052] Step 1-2, adding inorganic particles to the solution obtained in step 1-1, stirring under an inert atmosphere until completely dispersed, to obtain a polymer composite solution. In some embodiments, the inert atmosphere includes but is not limited to an argon atmosphere.

[0053] In some embodiments, in step 3, the step of forming the second modification layer includes: spin coating the polymer composite solution on the other side surface of the solid electrolyte, removing excess solvent, and obtaining the second modification layer. For example, in some embodiments, step 2 is repeated on the other side surface of the solid electrolyte to obtain the second modification layer; in other embodiments, when forming the second modification layer, the ratio of each component in the polymer composite solution obtained in step 1 is changed and / or the concentration of the polymer is changed, or the spin coating parameters in step 2 are adjusted to form a second modification layer with a suitable thickness and excellent morphology.

[0054] In some embodiments, the volume of the polymer composite solution used for each spin coating is 5 μL to 30 μL, and for example, the volume of the polymer composite solution used for each spin coating is 5 μL, 6 μL, 8 μL, 10 μL, 12 μL, 14 μL, 15 μL, 16 μL, 18 μL, 20 μL, 22 μL, 24 μL, 25 μL, 26 μL, 28 μL, 30 μL, or a range consisting of any two of the above values. In some embodiments, the volume of the polymer composite solution used for each spin coating is 15 μL to 25 μL; for example, the volume of the polymer composite solution used for each spin coating is 15.5 μL, 17 μL, 19 μL, 21 μL, 23 μL, 24.5 μL, or a range consisting of any two of the above values.

[0055] It is understandable that if too little polymer composite solution is used for each spin coating, it will not be enough to completely cover the surface of the solid electrolyte; if too much polymer composite solution is used for each spin coating, it will lead to a waste of raw materials, and the excess will also cause the first modification layer or the second modification layer to be too thick, thereby increasing the conduction time of lithium ions in the first modification layer or the second modification layer, increasing the kinetic loss, and thus deteriorating the cycle performance of the battery. Controlling the volume of the polymer composite solution used for each spin coating within the above range is conducive to forming a dense and uniform modification layer with appropriate thickness, thereby improving the electrochemical performance and cycle performance of the secondary battery.

[0056] In some embodiments, the rotation speed of each spin coating is 20rpm / min to 80rpm / min. Exemplarily, the rotation speed of each spin coating is 20rpm / min, 25rpm / min, 30rpm / min, 35rpm / min, 40rpm / min, 45rpm / min, 50rpm / min, 55rpm / min, 60rpm / min, 65rpm / min, 70rpm / min, 75rpm / min, 80rpm / min or a range consisting of any two of the above values.

[0057] It is understandable that if the rotation speed of each spin coating is too high, the thickness of the first modification layer and / or the second modification layer will be too thin; and if the rotation speed of each spin coating is too low, the uniformity of the first modification layer and / or the second modification layer will be poor. Controlling the rotation speed of each spin coating within the above range is conducive to controlling the balance between the thickness and uniformity of the first modification layer and / or the second modification layer, reducing the interface defects between the electrode and the solid electrolyte, and thus helping to improve the electrochemical performance and cycle performance of the secondary battery.

[0058] In some embodiments, the viscosity of the polymer composite solution is 1000 cP to 4000 cP; illustratively, the viscosity of the polymer composite solution is 1000 cP, 1200 cP, 1400 cP, 1500 cP, 1600 cP, 1800 cP, 2000 cP, 2200 cP, 2400 cP, 2500 cP, 2600 cP, 2800 cP, 3000 cP, 3200 cP, 3400 cP, 3500 cP, 3600 cP, 3800 cP, 4000 cP or a range consisting of any two of the above values. If the viscosity of the polymer composite solution is too large, the uniformity of the first modified layer and / or the second modified layer formed is poor, and the interface performance is deteriorated; if the viscosity of the polymer composite solution is too small, the spin coating process is difficult to implement, or the thickness of the first modified layer and / or the second modified layer formed is too thin, and it is difficult to achieve an effective interface improvement effect.

[0059] In some embodiments, based on the mass of the polymer composite solution, the mass content of the polymer is 8wt% to 30wt%; exemplary, based on the mass of the polymer composite solution, the mass content of the polymer is 8wt%, 10wt%, 15wt%, 20wt%, 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, 30wt% or a range consisting of any two of the above values. The polymer concentration is positively correlated with the viscosity of the polymer composite solution. Too high a polymer concentration will cause the viscosity of the polymer composite solution to be too large, which is not easy to spread, and is not conducive to the uniform film formation of the polymer composite solution on the surface of the solid electrolyte, so that the first modified layer and the second modified layer formed have poor uniformity, which will degrade the interface performance between the electrode and the solid electrolyte; too low a polymer concentration will cause the viscosity of the polymer composite solution to be too low, the fluidity of the polymer composite solution to be too large, and it is not easy to form a film on the surface of the solid electrolyte, and it cannot be applied to the spin coating process. And it will cause the polymer composite solution to have a long curing time on the surface of the solid electrolyte, and the inorganic particles will show a stratification phenomenon, thereby degrading the performance of the modified layer.

[0060] In some embodiments, the mass content of the polymer is 10 wt % to 25 wt % based on the mass of the polymer composite solution. Exemplarily, the mass content of the polymer is 10.5 wt %, 11 wt %, 12 wt %, 13 wt %, 14 wt %, 15.5 wt %, 16 wt %, 17 wt %, 18 wt %, 19 wt %, 20.5 wt %, 21 wt %, 22 wt %, 23 wt %, 24 wt %, 24.5 wt % or a range consisting of any two of the above values ​​based on the mass of the polymer composite solution.

[0061] In some embodiments, the polymer includes, but is not limited to, at least one of polyvinylidene fluoride, polyethylene oxide, polyacrylonitrile, and polymethyl acrylate.

[0062] In some embodiments, the material of the inorganic particles includes, but is not limited to, at least one of aluminum nitride, aluminum oxide, boron nitride, magnesium hydroxide, calcium hydroxide, and silicon dioxide.

[0063] In some embodiments, the mass content of the inorganic particles is 5wt% to 50wt% based on the total mass of the polymer and the inorganic particles. Exemplarily, the mass content of the inorganic particles is 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt% or a range consisting of any two of the above values ​​based on the total mass of the polymer and the inorganic particles. In some embodiments, based on the total mass of the polymer and the inorganic particles, the mass content of the inorganic particles is 15wt% to 40wt%, more preferably, based on the total mass of the polymer and the inorganic particles, the mass content of the inorganic particles is 20wt% to 40wt%; exemplarily, based on the total mass of the polymer and the inorganic particles, the mass content of the inorganic particles is 21wt%, 22wt%, 23wt%, 24wt%, 26wt%, 27wt%, 28wt%, 29wt%, 31wt%, 32wt%, 33wt%, 34wt%, 36wt%, 37wt%, 38wt%, 39wt%, 40wt% or a range consisting of any two of the above values.

[0064] In some embodiments, the average particle size of the inorganic particles is 20 nm to 200 nm. Exemplarily, the average particle size of the inorganic particles is 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm, or a range consisting of any two of the above values.

[0065] In some embodiments, the average particle size of the inorganic particles is 30 nm to 150 nm; illustratively, the average particle size of the inorganic particles is 32 nm, 35 nm, 45 nm, 55 nm, 65 nm, 75 nm, 85 nm, 95 nm, 105 nm, 115 nm, 125 nm, 135 nm, 145 nm, 150 nm or a range consisting of any two of the above values.

[0066] In some embodiments, the lithium salt includes but is not limited to at least one of lithium nitrate, lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide), lithium perchlorate, lithium difluorooxalatoborate, and lithium trifluoromethanesulfonate.

[0067] In some embodiments, the lithium salt includes lithium bis(trifluoromethanesulfonyl)imide.

[0068] In some embodiments, the concentration of the lithium salt in the polymer composite solution is 0.5 mol / L to 2.5 mol / L. Exemplarily, the concentration of the lithium salt in the polymer composite solution is 0.5 mol / L, 0.6 mol / L, 0.8 mol / L, 1.0 mol / L, 1.2 mol / L, 1.4 mol / L, 1.5 mol / L, 1.6 mol / L, 1.8 mol / L, 2.0 mol / L, 2.2 mol / L, 2.4 mol / L, 2.5 mol / L or a range consisting of any two of the above values.

[0069] It is understandable that if the lithium salt concentration is too low, the ionic conductivity of the first modification layer and / or the second modification layer will decrease, and it may also lead to uneven distribution of lithium ions and unstable electrochemical interface; if the lithium salt concentration is too high, the viscosity of the polymer composite solution will be too high, the fluidity will be insufficient, and the uniformity of the formed first modification layer and / or the second modification layer will deteriorate, affecting the lithium ion transmission rate between the positive electrode and / or the negative electrode and the solid electrolyte, and also increasing the risk of decomposition / degradation of the first modification layer and / or the second modification layer. Controlling the lithium salt concentration within the above range can ensure that lithium ions are quickly conducted in the first modification layer and / or the second modification layer, thereby helping to improve the overall performance of the secondary battery.

[0070] In some embodiments, the solvent includes, but is not limited to, N-methylpyrrolidone or dimethylformamide.

[0071] In some embodiments, the mass content of the solvent is 60 wt % to 90 wt % based on the mass of the polymer composite solution. Exemplarily, the mass content of the solvent is 60 wt %, 65 wt %, 70 wt %, 75 wt %, 80 wt %, 85 wt %, 90 wt % or a range consisting of any two of the above values ​​based on the mass of the polymer composite solution.

[0072] In some embodiments, methods for removing excess solvent include, but are not limited to, vacuum drying.

[0073] In some embodiments, the vacuum drying temperature is 25°C to 80°C. Exemplarily, the vacuum drying temperature is 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C or a range consisting of any two of the above values.

[0074] It is understandable that if the vacuum drying temperature is too low, the solvent evaporates slowly, making the preparation time too long; while if the vacuum drying temperature is too high, the solvent evaporates quickly, which will cause the viscosity of the liquid film formed after the polymer composite solution is coated to increase too quickly, so that the formed modified layer has more pinholes or even forms a morphology similar to "orange peel", thereby deteriorating the performance of the secondary battery. Controlling the vacuum drying temperature within the above range can take into account both the preparation time and film formation, which is conducive to the realization of practical applications in business.

[0075] In some embodiments, the vacuum drying time is 6 h to 12 h. Exemplarily, the vacuum drying time is 6 h, 6.5 h, 7 h, 7.5 h, 8 h, 8.5 h, 9 h, 9.5 h, 10 h, 10.5 h, 11 h, 11.5 h, 12 h or a range consisting of any two of the above values.

[0076] It is understandable that the vacuum drying time is negatively correlated with the vacuum drying temperature. The higher the vacuum drying temperature, the shorter the vacuum drying time, and the lower the vacuum drying temperature, the longer the vacuum drying time.

[0077] 3. Device

[0078] One or more embodiments of the present application further provide a device including the secondary battery of the aforementioned embodiment.

[0079] In some embodiments, the devices of the present application include but are not limited to: laptop computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD televisions, portable cleaners, portable CD players, mini CDs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries or lithium-ion capacitors, etc.

[0080] The technical solution of the present application will be further described below in conjunction with specific examples and comparative examples. The following examples and comparative examples are only used to exemplify the inventive concept of the present application and are not used to limit the present application.

[0081] Examples and Comparative Examples

[0082] Example 1

[0083] Preparation of positive electrode

[0084] The positive electrode active material LiNi 0.5 Co 0.2 Mn 0.3O2(NCM523), conductive agent carbon nanotube / acetylene black, binder polyvinylidene fluoride PVDF, by weight proportion LiNi 0.5 Co 0.2 Mn 0.3 O2:CNT / Super-P:PVDF=95:2.0 / 1.0:2 was fully slurried in N-methylpyrrolidone (NMP) solvent system, coated on a 12 μm thick aluminum current collector, dried, and roll-pressed to obtain a positive electrode sheet.

[0085] Preparation of negative electrode

[0086] A lithium metal sheet with a diameter of 12 mm and a thickness of 0.3 mm was cut as the negative electrode sheet.

[0087] Preparation of solid electrolyte

[0088] Step 1: Add TiOSO4 to deionized water, mix, and prepare a TiOSO4 aqueous solution; adjust the pH value to prepare a TiOSO4 aqueous solution for later use; add NaF to deionized water to prepare a NaF aqueous solution for later use; add H3PO4 to deionized water to prepare a H3PO4 aqueous solution for later use;

[0089] Step 2: Add deionized water, NaF and H2SO4 into a reaction kettle to obtain a mixed aqueous solution, heat it, and add the TiOSO4 solution, NaF solution and H3PO4 solution obtained in step 1 at the same time, separate the solid and the liquid, wash and dry the obtained solid, and obtain Ti3(PO4)3 solid powder;

[0090] Step 3: Add AlPO4 solid and Li3PO4 solid to Ti3(PO4)3 solid powder, mix, sinter, crush and sieve to obtain LATP particles; then hot press the LATP particles to obtain Li 1.3 Al 0.3 Ti 1.7 (PO4)3(LATP) solid electrolyte sheet.

[0091] Preparation of the first and second modified layers

[0092] Step 1: Change the molecular weight M w600000 g / mol polyethylene oxide (PEO) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) are added to N-methylpyrrolidone, and the polymer and lithium salt are completely dissolved by magnetic stirring under argon protection, and then 30 nm boron nitride (BN) powder is added to the above stirred solution, and the BN powder is evenly dispersed in the mixed solution by magnetic stirring under argon protection to obtain a final polymer composite solution, wherein PEO: LiTFSI: BN = 53.73%: 40.30%: 5.96%, and the mass content of the polymer in the composite solution is 15wt%;

[0093] Step 2: Set the rotation speed of the rotator to 60 rpm / min, drop 20 μL of the polymer composite solution obtained in step 1 on one side of the LATP inorganic solid electrolyte, spin coat to form a film, and then dry it in a vacuum environment at 25°C for 12 hours to obtain the first modified layer;

[0094] Step three, repeat step two on the other side of the solid electrolyte to obtain a second modified layer.

[0095] Assembly of secondary batteries

[0096] Sequentially place the prepared NCM523 positive electrode sheet, the LATP solid electrolyte containing the dried first and second modified layers, and the lithium metal negative electrode sheet into the CR2032 positive electrode shell, adjust the positive electrode sheet, the negative electrode sheet, and the solid electrolyte in the center of the positive electrode shell, and then cover the CR2032 negative electrode shell, wherein the first modified layer is located between the positive electrode sheet and the solid electrolyte, and the second modified layer is located between the negative electrode sheet and the solid electrolyte. Place the assembled button battery into the button battery sealing machine mold, set the pressure to 800Pa for pressing, and the secondary battery in the embodiment can be obtained.

[0097] Example 2-3

[0098] The only difference between Example 2-3 and Example 1 is that the mass ratio of PEO, LiTFSI and BN is changed, see Table 1 for details.

[0099] The rest of the preparation method is the same as that in Example 1.

[0100] Embodiment 4-6

[0101] The only difference between Example 4-6 and Example 3 is that the rotation speed used during spin coating is changed, see Table 1 for details.

[0102] The rest of the preparation method is the same as that in Example 3.

[0103] Example 7

[0104] The only difference between Example 7 and Example 6 is that when forming the first modification layer and the second modification layer, the temperature and time of the vacuum drying treatment are changed, see Table 1 for details.

[0105] The rest of the preparation method is the same as that in Example 6.

[0106] Embodiment 8-9

[0107] The only difference between Example 8-9 and Example 7 is that the type of polymer is changed, see Table 1 for details.

[0108] The rest of the preparation method is the same as Example 7.

[0109] Example 10

[0110] The only difference between Example 10 and Example 7 is that the vacuum drying time is prolonged when forming the modification layer.

[0111] The rest of the preparation method is the same as Example 7.

[0112] Examples 11-18

[0113] The only difference between Examples 11-18 and Example 7 is that the types of inorganic particles are changed, see Table 1 for details.

[0114] The rest of the preparation method is the same as Example 7.

[0115] Examples 19-20

[0116] The only difference between Examples 19-20 and Example 7 is that during spin coating, the amount of the polymer composite solution used is changed.

[0117] The rest of the preparation method is the same as Example 7.

[0118] Examples 21-22

[0119] The only difference between Examples 21-22 and Example 7 is that the mass ratio of PEO, LiTFSI and BN is changed, the polymer concentration in the composite solution is changed, and the viscosity of the polymer composite solution is changed. For details, see Table 1.

[0120] The rest of the preparation method is the same as Example 7.

[0121] Embodiment 23-24

[0122] The only difference between Example 23-24 and Example 7 is that the type of lithium salt is changed, see Table 1 for details.

[0123] The rest of the preparation method is the same as Example 7.

[0124] Comparative Example 1

[0125] The only difference between Comparative Example 1 and Example 7 is that neither the first modification layer nor the second modification layer is formed on the surface of the solid electrolyte.

[0126] The rest of the preparation method is the same as Example 7.

[0127] Comparative Example 2

[0128] The only difference between Comparative Example 2 and Example 7 is that, in the secondary battery, only the first modified layer (on the positive electrode sheet side) is formed between the positive electrode sheet and the solid electrolyte, and the second modified layer is not formed.

[0129] The rest of the preparation method is the same as Example 7.

[0130] Comparative Example 3

[0131] The only difference between Comparative Example 3 and Example 7 is that, in the secondary battery, only the second modified layer (on the negative electrode sheet side) is formed between the negative electrode sheet and the solid electrolyte, and the first modified layer is not formed.

[0132] The rest of the preparation method is the same as Example 7.

[0133] Comparative Example 4

[0134] The only difference between Comparative Example 4 and Example 7 is that the concentration of the polymer is too large.

[0135] The rest of the preparation method is the same as Example 7.

[0136] Comparative Example 5

[0137] The only difference between Comparative Example 5 and Example 7 is that no inorganic particles are added to the polymer composite solution.

[0138] The rest of the preparation method is the same as Example 7.

[0139] Test Method

[0140] 1. Lithium cycle time

[0141] The LATP inorganic solid electrolyte containing the modified layer prepared in the comparative example and the embodiment was assembled with a lithium metal electrode into a lithium battery. -2 The lithium metal stability test was carried out at a current density of , and the voltage stability maintenance time (h) was recorded, which is recorded in Table 1.

[0142] 2. Capacity retention rate after 100 cycles at 25°C

[0143] The LATP inorganic solid electrolyte containing a modified layer obtained in the comparative example and the embodiment was assembled into a button-type full battery with a lithium metal negative electrode sheet and an NCM523 positive electrode sheet. The voltage range was set to 2.5V-4.3V and the current density parameter was set to 0.1C. The cycle capacity of the LATP inorganic solid electrolyte containing a modified layer obtained in different embodiments corresponding to the ternary positive electrode full battery was recorded, and the capacity retention rate of 100 cycles was compared and recorded in Table 1.

[0144] 3. Capacity retention rate after 100 cycles at 45°C

[0145] The LATP inorganic solid electrolyte containing a modified layer obtained in the comparative example and the embodiment was assembled into a button-type full battery with a lithium metal negative electrode sheet and an NCM523 positive electrode sheet. The voltage range was set to 2.5V-4.3V and the current density parameter was set to 0.1C. The cycle capacity of the LATP inorganic solid electrolyte containing a modified layer obtained in different embodiments corresponding to the ternary positive electrode full battery was recorded, and the capacity retention rate of 100 cycles was compared and recorded in Table 1.

[0146] 4. Thickness of the finishing layer

[0147] The thickness of the LATP inorganic solid electrolyte is recorded as D1 using a spiral thickness gauge; the polymer composite solution required in the embodiment is added dropwise to the LATP inorganic solid electrolyte, and after the solvent is evaporated, the thickness of the LATP inorganic solid electrolyte containing the modified layer is recorded as D2 using a spiral thickness gauge; the total thickness of the modified layer is: D2-D1.

[0148] 5. Ionic conductivity of the first and second modified layers

[0149] The polymer composite solution involved in different embodiments is added dropwise to a glass vessel with a diameter of 12 cm, and the solvent is dried at 70°C under a protective atmosphere to form the corresponding first modification layer and / or second modification layer. Cut the first modification layer and / or second modification layer of appropriate size, with an area of ​​S, and record its thickness d by a thickness gauge. Assemble a stainless steel / modification layer (first modification layer and / or second modification layer) / stainless steel symmetrical battery, place it in a 60°C oven, and record its impedance R (10mHZ~100KHZ; 10mV) by an electrochemical workstation. 60°C modification layer ion conductivity: d / RS.

[0150] Referring to Table 1 and Table 2, it can be seen from the data of Comparative Example 1 that, without using the first modification layer and / or the second modification layer of the present application, the lithium cycle time and high and low temperature cycle performance of the secondary battery are both poor. The possible reason is that the solid-solid interface between the solid electrolyte and the electrode is relatively rough, the contact area is small, and there are many interface defects, resulting in a large internal resistance of the secondary battery, which makes the electrochemical performance of the secondary battery deteriorate rapidly during the cycle. It can be seen from the data of Comparative Examples 2 and 3 that when the first modification layer or the second modification layer is used on one side of the lithium battery, the lithium cycle time is extended, and the high and low temperature cycle performance is still very poor. It can be seen from the data of Examples 1-25 that after the first modification layer and the second modification layer are formed at the same time, the lithium cycle time and high and low temperature cycle performance of the secondary battery are significantly improved. Further, referring to the data of Example 7 and Comparative Examples 2 and 3, compared with forming the first modification layer or the second modification layer only on one side of the solid electrolyte surface, after the first modification layer and the second modification layer are respectively formed on both sides of the solid electrolyte surface, the lithium cycle performance and the high and low temperature cycle performance are significantly improved; and, the effect obtained by respectively forming the first modification layer and the second modification layer on both sides of the solid electrolyte is not a simple superposition of the effects that can be obtained by forming the first modification layer or the second modification layer on one side of the solid electrolyte surface alone; that is, compared with forming the first modification layer or the second modification layer only on one side of the solid electrolyte surface, forming the first modification layer and the second modification layer on both sides of the solid electrolyte surface respectively has achieved unexpected progress.

[0151] Referring to Comparative Example 4 and Comparative Example 1 and Example 7, when the content of the polymer in the first modification layer and the second modification layer is too high, although it can also improve the lithium cycle performance and high and low temperature cycle performance of the secondary battery to a certain extent, the effect is limited. The reason is that the high polymer content makes the viscosity of the polymer composite solution too large, which is not easy to spread, and is not conducive to the uniform film formation of the polymer composite solution on the surface of the solid electrolyte, so that the first modification layer and the second modification layer formed have poor uniformity, which will deteriorate the interface performance between the electrode and the solid electrolyte; at the same time, it will cause the thickness of the first modification layer and the second modification layer to increase significantly, extending the transmission distance of lithium ions.

[0152] In addition, referring to Comparative Example 5 and Comparative Example 1 and Example 7, when inorganic particles are not added to the first modification layer and the second modification layer, the lithium cycle performance and low temperature cycle performance of the secondary battery can also be improved, but the effect is limited; and when inorganic particles are used in the first modification layer and the second modification layer, the improvement of the performance of the secondary battery is particularly significant. The possible reason is that the addition of inorganic particles can act as a plasticizer, which can reduce the crystallinity of the polymer or make its crystal disordered, which is beneficial to ion conduction. In addition, the chemical, electrochemical stability and thermal stability of the inorganic particles themselves can improve the high temperature safety and stability of the battery; the high strength of the inorganic particles can effectively inhibit the growth of lithium dendrites and improve the lithium stability of the solid electrolyte, thereby improving the lithium cycle performance of the battery.

[0153] Although some exemplary embodiments of the present application have been illustrated and described, the present application is not limited to the disclosed embodiments. On the contrary, those skilled in the art will recognize that some modifications and changes may be made to the described embodiments without departing from the spirit and scope of the present application as described in the appended claims.

[0154] Table 1

[0155]

[0156]

[0157] Table 2

[0158]

[0159]

[0160] Failed: indicates that before 100 cycles at 25°C, the capacity retention rate of the solid-state lithium battery in this example has decayed to below 60%.

[0161] Thickness: refers to the total thickness of the first modified layer and the second modified layer on both sides of the solid electrolyte interface layer.

Claims

1. A secondary battery, characterized in that: It includes a positive electrode sheet, a negative electrode sheet, a solid electrolyte, a first modification layer and a second modification layer; one of the first modification layer and the second modification layer is located between the positive electrode sheet and the solid electrolyte, and the other of the first modification layer and the second modification layer is located between the negative electrode sheet and the solid electrolyte; the first modification layer and / or the second modification layer includes a polymer with a mass content of 20wt% to 60wt%, a lithium salt of 10wt% to 65wt% and inorganic particles of 2wt% to 45wt%.

2. The secondary battery according to claim 1, characterized in that: The first modified layer and / or the second modified layer comprises 30wt% to 50wt% of polymer, 20wt% to 50wt% of lithium salt and 20wt% to 40wt% of inorganic particles.

3. The secondary battery according to claim 1, characterized in that: At least one of the following conditions is also met: (a) The ionic conductivity of the first modified layer and / or the second modified layer at 60°C is 1.5×10 -3 S cm -1 ~5.0×10 -3 S cm -1 ; (b) at least one of the first modified layer and the second modified layer has a thickness of 60 μm to 100 μm; (c) The first modification layer and the second modification layer both include a polymer with a mass content of 20wt% to 60wt%, a lithium salt of 10wt% to 65wt% and inorganic particles of 2wt% to 45wt%, the first modification layer is located between the positive electrode plate and the solid electrolyte, the second modification layer is located between the negative electrode plate and the solid electrolyte, and the thickness ratio of the first modification layer to the second modification layer is 1:(1.00 to 1.67).

4. The secondary battery according to claim 1, characterized in that: At least one of the following conditions is also met: (d) the average particle size of the inorganic particles is 20 nm to 200 nm; (e) Based on the total mass of the polymer and the inorganic particles, the mass content of the inorganic particles is 5 wt % to 50 wt %.

5. The secondary battery according to claim 4, characterized in that: At least one of the following conditions is also met: (f) the average particle size of the inorganic particles is 30 nm to 150 nm; (g) Based on the total mass of the polymer and the inorganic particles, the mass content of the inorganic particles is 20 wt % to 40 wt %.

6. The secondary battery according to any one of claims 1 to 5, characterized in that: At least one of the following conditions is also met: (h) the polymer comprises at least one of polyvinylidene fluoride, polyethylene oxide, polyacrylonitrile and polymethyl acrylate; (i) the lithium salt comprises at least one of lithium nitrate, lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium bis(trifluoromethanesulfonylimide), lithium bis(fluorosulfonylimide), lithium perchlorate, lithium bis(difluorooxalatoborate) and lithium trifluoromethanesulfonate; (j) the inorganic particles include at least one of aluminum nitride, aluminum oxide, boron nitride, magnesium hydroxide, calcium hydroxide, and silicon dioxide; (k) The solid electrolyte includes at least one of a polymer solid electrolyte, an oxide solid electrolyte or a sulfide solid electrolyte; preferably, the oxide solid electrolyte includes at least one of a NASICON type electrolyte, a garnet type electrolyte and a perovskite type electrolyte; preferably, the oxide solid electrolyte includes Li 1.3 Al 0.3 Ti 1.7 (PO4)3, Li7La3Zr2O 12 and Li 0.35 La 0.55 At least one of TiO3.

7. A method for preparing a secondary battery, characterized in that: For preparing a secondary battery according to any one of claims 1 to 6, the preparation method comprising: Step 1, mixing a mixture including 20wt% to 60wt% of a polymer, 10wt% to 65wt% of a lithium salt and 2wt% to 45wt% of inorganic particles with a solvent to prepare a polymer composite solution; Step 2, coating the polymer composite solution obtained in step 1 on one surface of the solid electrolyte, removing excess solvent, and obtaining a first modified layer; Step 3, forming a second modified layer on the other side surface of the solid electrolyte.

8. The method for preparing a secondary battery according to claim 7, characterized in that: The coating method in step 2 includes spin coating; and / or In step 3, the step of forming the second modified layer includes: spin coating the polymer composite solution on the other side surface of the solid electrolyte, removing excess solvent, and obtaining the second modified layer.

9. The preparation method according to claim 8, characterized in that: At least one of the following conditions is also met: (l) the volume of the polymer composite solution used in each spin coating is 5 μl to 30 μl; (m) The rotation speed of each spin coating is 20 rpm / min to 80 rpm / min; (n) the viscosity of the polymer composite solution at 25° C. is 1000 cP to 4000 cP; (o) Based on the mass of the polymer composite solution, the mass content of the polymer is 8 wt % to 30 wt %.

10. A device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 1 to 6 or a secondary battery prepared by the preparation method according to any one of claims 7 to 9.

Citation Information

Cited By

  • Interface modification material with high failure threshold value, solid electrolyte and all-solid-state battery

    CN120073052A

  • Lithium metal battery and preparation method thereof, negative pole piece and power utilization device

    CN120767369A

  • Modified coating, preparation method, coating-modified pole piece and battery

    CN121506965A

  • A modified coating, a preparation method, an electrode with modified coating, and a battery.

    CN121506965B